Dexmedetomidine Exerted Anti-arrhythmic Effects in Rat With Ischemic Cardiomyopathy via Upregulation of Connexin 43 and Reduction of Fibrosis and Inflammation - Wu, Shu-jie; Lin, Zhong-hao; Lin, Yuan-zheng; Rao, Zhi-heng; Lin, Jia-feng; Wu, Lian-pin; Li, Lei (Frontiers in Physiology, 2020)
Background Persistent myocardial ischemia post-myocardial infarction can lead to fatal ventricular arrhythmias such as ventricular tachycardia and fibrillation, both of which carry high mortality rates. Dexmedetomidine (Dex) is a highly selective α2-agonist used in surgery for congenital cardiac disease because of its antiarrhythmic properties. Dex has previously been reported to prevent or terminate various arrhythmias. The purpose of the present study was to determine the anti-arrhythmic properties of Dex in the context of ischemic cardiomyopathy (ICM) after myocardial infarction. Methods and Results We randomly allocated 48 rats with ICM, created by persistent ligation of the left anterior descending artery for 4 weeks, into six groups: Sham (n = 8), Sham + BML (n = 8), ICM (n = 8), ICM + BML (n = 8), ICM + Dex (n = 8), and ICM + Dex + BML (n = 8). Treatments started after ICM was confirmed (the day after echocardiographic measurement) and continued for 4 weeks (inject intraperitoneally, daily). Dex inhibited the generation of collagens, cytokines, and other inflammatory mediators in rats with ICM via the suppression of NF-κB activation and increased the distribution of connexin 43 (Cx43) via phosphorylation of adenosine 5′-monophosphate-activated protein kinase (AMPK). Dex reduced the occurrence of spontaneous ventricular arrhythmias (ventricular premature beat or ventricular tachycardia), decreased the inducibility quotient of ventricular arrhythmias induced by PES, and partly improved cardiac contraction. The AMPK antagonist BML-275 dihydrochloride (BML) partly weakened the cardioprotective effect of Dex. Conclusion Dex conferred anti-arrhythmic effects in the context of ICM via upregulation of Cx43 and suppression of inflammation and fibrosis. The anti-arrhythmic and anti-inflammatory properties of Dex may be mediated by phosphorylation of AMPK and subsequent suppression of NF-κB activation.